Cattle olfaction: Dairy cows' interest in odors and factors affecting their odor exploration behavior - Maria Vilain R⊘rvang; Erika Harainen; Niclas Högberg; Johanna Stenfelt (Journal of Dairy Science)
ABSTRACT: Animals use their sense of smell in various situations, including foraging, selecting mates, and assessing predation risks. Consequently, odors are likely to affect farm animals in numerous handling and management practices. Cattle have a well-developed sense of olfaction that may play a larger role in their everyday life than is currently considered. The current body of research on cattle olfactory abilities is, however, surprisingly scarce. The aim of this study was to investigate if cows can detect and discriminate 4 odors of natural, nonsocial origin, and if any of the specific odors evoke more interest (measured as sniffing time) than others. We further aimed to assess if age, parity, and breed affected this. In addition, we investigated olfactory-exploration behavior (other than sniffing: licking, biting, flehmen, head movements, backing, snorting) of dairy cattle and ear positions to elucidate if certain behaviors and ear positions were restricted to certain odors. Twenty-eight cows (16 Swedish Holstein, 12 Swedish Red) were enrolled in a habituation-dishabituation test where they were tested in pairs on 4 natural odors (essential oils, nondiluted): cedarwood, lavender, orange, and peppermint. The test was conducted on individual animals in their home environment where each odor was presented 3 times in a row for 1 min each with an intertrial interval of 2 min. Following another 2-min interval without the first odor, the cow was presented with a different odor, with order of odor presentation balanced among animals. Duration of sniffing (muzzle in proximity to) the odor box, occurrence of licking or biting the odor box, and avoidance behavior (e.g., backing and head movements), and ear positions were recorded. Although the results showed a decrease in sniffing time over repeated presentations of the same odor, only the first-to-third presentation of cedarwood and first-to-second and first-to-third presentation of orange differed significantly. Only some dishabituation trials elicited a significant reinstatement of sniffing; hence, it is unclear if cows were able to discriminate all odors from each other. Testing cows in pairs potentially led to brief pre-exposure to odors, thereby affecting overall sniffing durations. More studies are thus needed to elucidate if cows can recognize but also discriminate the odors. Cows did not show a clear interest in any particular odor, though they numerically sniffed cedarwood the most and orange the least. Younger cows expressed more sniffing behavior than older cows regardless of odor, and younger cows also expressed axial ear positions for longer. Specific odors did not elicit more of any of the ear positions than others. Behaviors indicative of avoidance reactions (head movements, backing, snorting) were generally low for all odors, but Swedish Holstein cows expressed more backward ear positions than Swedish Red, highlighting the need for further studies including various cattle breeds. We encourage future studies on olfactory abilities and preferences, as well as refinement of methods to further adapt testing regimens for cattle olfaction.